Imports and oligopoly behaviour in Australian manufacturing - Chong, Han (Curtin University, 2003)
Oligopoly behaviour by domestic firms faced with foreign competition in a small open economy is examined in the context of a market for differentiated products. This paper concentrates on the responsiveness of import flows to import price in the context of trade with imperfect competition. The empirical work analyses the behaviour over time of the interaction between domestic industry prices and domestic costs as well as foreign competitors' prices. A structural model is employed for estimation purposes with consumer demand derived from a CES (constant elasticity of substitution) utility function of domestic and foreign composites of goods. Domestic firms are assumed to face Leontief production functions and maximise profit independently subject to their conjectures about the reactions of rivals. Firm behaviour is modelled using conjectural variations to identify market power, distinguishing two models of oligopoly, namely, Cournot and Bertrand conjectural variations. This leads to the econometric specification of pricing, import and budget share equations consistent with oligopolistic equilibrium. The interrelationship between the budget share equations and the price-cost margin provides encompasses either Cournot or Bertrand conjectural variations. The econometric specification is applied to each of the two digit Australian manufacturing industries using quarterly data covering the period from 1984 to 2000. Results of the industrial behaviour indicate that industries that produce consumer products are generally react to price movements The classification of industry 21 to 24 is more proximate to consumer products as compared to higher industrial numbering. The regression results for industry 25 to 28 suggest quantity reactions. This is in line with the nature of the products produce by these industries, which are heavy industrial manufacturing products.The elasticity with respect to foreign price is distinguished between the "partial" and the "total" effect. The partial elasticity of import demand ranges from .6205 to 4.9497, while the total elasticity of import demand ranges from .6505 to 19.8132. The elasticity of demand ranges from .0191 for Wood and Paper Product manufacturing to 3.4093 for Food, Beverage and Tobacco manufacturing.